DEVELOPING WORKSHEET BASED DISCOVERY LEARNING ON THE STRUCTURE AND FUNCTION OF ORGAN TISSUESÂ OF PLANT IN THE SENIOR HIGH SCHOOL ON THE 11TH - ROBELINA A, DEVI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Structure and function of organ tissues of plant sub subject that can not be explained by lectures and reading books. So, be needed the worksheet that can to help students in order to active role in learning. One of the ways is developing worksheet based discovery learning. The developing aims to know the advisability of the worksheet in empiris and teoritis, to know the legibility of the worksheet, to describe result of student learning after used worksheet, to know students activity during used worksheet, and to describe student response which had developed. This study is development research. Target of research is the worksheet based discovery learning in structure and function of organ tissues of plant sub subject that is tested to sixteen students in senior high school 1 Dander. Based on the result of research, obtained some following result: 1) The advisability of the worksheet is very good and advisable to used, 2) The result of student learning is 87,5% complete in cognitive competence and 74,30% complete in aim learning, 3) The legibility of the worksheet is very advisable, and 4) students give positive responses to worksheet is developed. Keywords: student worksheet, discovery learning, Structure and function of organ tissues of plant.